PBM 110 - Communication in Practical Business Management - Linn Benton Virtual College (2018)
In this course students will develop oral and written communication skills that will allow a business professional to communicate effectively with customers, clients, and employees. Students will develop and deliver effective presentations using presentation software, learn negotiating skills, and practice extemporaneous speaking. Students will craft effective emails, product descriptions, resumes, and other business-related writing and oral communication skills. Students will practice skills needed to effectively apply and interview for jobs.